“Palliative care is so much more than that”: a qualitative study exploring experiences of hospice staff and bereaved carers during the COVID-19 pandemic - Bailey, Cara; Guo, Ping; MacArtney, John; Finucane, Anne; Meade, Richard; Swan, Susan; Wagstaff, Ellie (Frontiers in Public Health, 2023)
Background The way in which end-of-life care was provided changed significantly during the first two-years of the covid-19 pandemic. The national lockdown restrictions reduced formal care support services and increased the burden upon many carers taking on the caring role for the first time. We aimed to explore decision-making about place of care during the covid-19 pandemic, and the impact on experience from the perspectives of carers and hospice staff caring for people at the end-of-life. Methods A qualitative study using virtual interviews was conducted between October 2020-April 2021. Data were analysed thematically using framework analysis, an analytical framework that enables qualitative research to be organised into defined themes derived from the research question. Findings were presented to stakeholders in policy round tables between March 2022 – March 2023 and discussed collaboratively with staff, stakeholders and the public to inform policy and practice change. Findings 37 participants (15 bereaved carers and 22 staff) recruited via hospice services in England and Scotland. Four key themes were identified: (1) Changing preferences relating to decision-making about place of care, and the impact at the time of death and into bereavement; (2) Missed opportunities related to not being there, not having others around and being robbed of memory-making; (3) The lone carer during a period of high intensity, and reduced home support; (4) Process vs person-centred care resulting from changing rules and restrictions, and prioritisation of regulations over essential palliative care. Conclusion The study provides valuable, global implications for all involved in end-of-life care. Despite great efforts to provide dignified, quality care, palliative care during the pandemic changed focusing on essential ‘physical care’. The psychological suffering experienced by staff and carers may need longer-term support mechanisms putting in place, which will benefit from a public health approach. Policy makers should consider improving carer identification, and resources for wider end-of-life care education to support the needs of carers, health and social care staff and citizens.